Of Labor’s Weave and Fortune’s Hand: Unraveling the Complexities of Workforce Dynamics in the UK - Al Owais, Abdelaziz; Joseph, Robinson; Ullah, Sami (International Journal of Economics and Financial Issues, 2025)
Internationalization of markets and migration challenges have unveiled various aspects of labor markets and sustainable practices. It is critical to comprehend how these phenomena are related and intertwined to address these issues with the right policies. This study has examined the impact of globalization, mass migration, and sustainable labor practices and provided valuable insights into the existing literature and policy formulation. Qualitative research methodology was employed in this study and data was collected by interviewing employer representatives, policymakers, and officials from labor unions. The data analysis involved thematic analysis of key themes and patterns. The findings of this study highlighted a complicated relationship among processes such as globalization, migration, and work sustainability and emphasized that globalization is both facilitating and constraining for organizations, and mass migration was understood as ensuring the supply of labor, threatening social fabric of host countries and creating precarious working conditions for migrants. It was also found that some of the sustainable labor practices were prioritized by policymakers, although they had different challenges in implementing them, especially in the case of migrant workers. This study also provided deep understanding of the impacts of globalization and international migration on migrants and their host countries socially, politically, economically and culturally. Hence, the need for sustainable and pro-migrant policies, and pro-maternal relations that protects the interests of both migrant laborers and employers. Thus, the findings and policy implications which were formulated by using Hofstede’s Dimensions theory and Carroll’s Pyramid theory can help policymakers and organizations work out effective strategies to address the consequences of these global processes on the global labor markets.